High-resolution wavenumber bandpass filtering of guided ultrasonic wavefield for the visualization of subtle structural flaws - Lee, Shi Yn; Romli, Fairuz Izzuddin; Mazlan, Norkhairunnisa; Lee, Jung-Ryul; Harmin, Mohammad Yazdi; Chia, Chen Ciang (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Guided ultrasonic wavefield propagation imaging (GUPI) is useful for visualizing hidden flaws in aerospace thin-walled structures, but the need for subjective signal processing involving three-dimensional Fourier transformation to increase the visibility of subtle flaws hinders its wider acceptance. A high-resolution wavenumber bandpass filter capable of consolidating subtle flaw-relevant information from a wide frequency band using only two-dimensional Fourier transformation was proposed. The filter overturns the long-standing belief that modes must be separated based on narrow-band data acquisition or processing to achieve high flaw visibility. Its characteristics and advantages were experimentally demonstrated through enhanced visualization of hidden wall-thinning flaws of a plate specimen. Its strength was further demonstrated through the first GUPI visualization of a partially loosened bolt, with unprecedented clarity to discern bolt tightness levels. The results conclusively proved that the proposed filter significantly enhances the resolution of GUPI within a structured processing framework.